Relationship Between Internet Scrolling Habit and Social Media Marketing (OCEM Journal of Management, Technology & Social Sciences, 2023)
The previous study has concluded that internet scrolling is required to generate business, and social media employs psychological techniques to advertise for business purposes. The primary objective of this study was to investigate the opinions and experiences of bachelor’s level students on the role of internet scrolling addiction impact on social media marketing. This study applied the quantitative approach and the survey instrument to collect data. The sample population was two hundred bachelor’s level students at Oxford College of Engineering and Management. A random sampling method was used to select sample students among three thousand studentsThe results show a significant association between internet scrolling habits and observing social media marketing, implying a negative association with using social media marketing (p < 0.05). Similarly, there was a positive association between social media marketing and influence on chatting apps (p < 0.05). Further, the results indicated a negative association between time of activeness and the use of social media with social media marketing. This study's implication would benefit social media marketers, students, scholars, entrepreneurs and owners of social media marketing businesses.